Mitral valve modelling and three-dimensional printing for planning and simulation of mitral valve repair. (6th September 2018) - Daemen, Jean H T; Heuts, Samuel; Olsthoorn, Jules R; Maessen, Jos G; Sardari Nia, Peyman
Abstract: OBJECTIVES: The aim of this study was to develop a process for modelling and 3-dimensional (3D) printing of different mitral valve diseases for procedural planning and simulation, based on 3D transoesophageal echocardiography (TOE). METHODS: 3D TOE was used to reconstruct a fully dynamic 3D view of the diseased valve. Reconstructions were cropped at the level of the valve and captured in mid-systole to assess the coaptation defect. Reconstructions were then exported as a surface mesh. To ensure a watertight and noise-reduced model, the mesh was processed using computer-modelling programmes, whereupon the valve was printed in 3D. For simulation purposes, deformable models were created based on negative mould fabrication and cast in tissue-mimicking silicone. Model validation was performed by intraoperative assessment of the valvular disease and repair strategy. RESULTS: The mitral valves of 10 prospective patients with different diseases were modelled. In 6 patients, a 3D printed rigid plastic mitral valve was created for procedural planning, and in 4 patients, a silicone-cast replica was created for procedural simulation. All models were created to scale, implying conservation of in vivo dimensions. Models were validated by in vivo comparison. Total workaround time ranged from 3 to 4 h and 2 to 3 days for rigid plastic and silicone models, respectively. Costs were €15 to €40 and €300, respectively. CONCLUSIONS: We demonstrated the feasibility of creating rigid plastic and tissue-mimicking silicone mitral valve replications. These models could be used in the future to enhance surgical anatomical interpretation, to facilitate planning and simulation of complex surgeries and for training purposes.